The 32nd Brazilian Society of Virology (SBV) 2021 Annual Meeting - Vaslin, Maite Freitas Silva; Leal, Alessandra Alevato; Bueno, Larissa Mayumi; Bittar, Cíntia [UNESP]; de Souza, Gabriela Fabiano [UNESP]; Lourenço, Karine; da Silva, Gustavo Peixoto Duarte; Guedes, Maria Isabel Maldonado Coelho; Proença-Módena, José Luiz; Junior, João Pessoa Araújo [UNESP]; Ferreira, Helena Lage; da Fonseca, Flávio Guimarães (MDPI, 2022)
The Brazilian Society of Virology has been organizing annual meetings for 32 years now. The 32nd annual meeting, which occurred in 2021, was once again an online meeting in consequence of the issues imposed by COVID-19, even with the vaccination advances. As in the 2020 meeting, the number of attendees was high, with considerable participation by undergraduate, graduate, and postdoc students. Distinguished scientists from different countries offered high-quality conferences, and oral presentation sessions were presented by young scientists showing their newest research results. For almost five hours a day during five days, attendees discussed high-quality science related to all areas of virology. Even with the difficulties imposed by another pandemic year, the 32nd SBV annual meeting achieved its most important goal—to inspire young scientists and discuss high-quality virology research.
Keywords: basic virology; Brazilian Society of Virology; environmental virology; human virology; invertebrate virology; plant virology; SBV; SBV annual meeting; veterinary virology